"Until they fit in." Maltese educators' practices and attitudes towards migrant students in middle and secondary schools. Issue 2 (28th December 2021) - Chircop, Louise
Abstract : Purpose: This paper aims to explore the attitudes of Maltese educators towards migrant students and how these attitudes impinge on their practices. Design/methodology/approach: A qualitative approach, informed by critical theory, was taken to conduct this study. Nineteen middle and secondary school educators were recruited through snowball sampling. In-depth semi-structured interviews were conducted to collect the data. Critical discourse analysis was used to analyze the data. Findings: The presence of migrant students in schools has caught the Maltese education system unprepared. As yet there are no policies to guide educators on practices that would enhance migrant students' sense of belonging. This paper shows how many of the educators engaged in exclusionary practices and argued that migrant students had to fit in within the present education system. While the language barrier was the greatest bone of contention, the presence of non-Catholic students was also seen as problematic. However, one could also observe accommodating practices and there were educators who embraced this diversity and implemented inclusive practices whenever possible. Originality/value: This study, locally new in its field, highlights the need for adequate training both in terms of pedagogies and methodologies that are inclusive, as well as professional development that targets the intellectual growth of educators in terms of exposure to sociological and philosophical theories, to become more conscious of the political implications of their actions and hopefully strive to create a more equitable educational experience for their students.